2021
DOI: 10.1186/s12910-021-00652-0
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Swedish physicians’ attitudes towards physician-assisted suicide: a cross-sectional study

Abstract: Aims To examine attitudes towards physician-assisted suicide (PAS) among physicians in Sweden and compare these with the results from a similar cross-sectional study performed in 2007. Participants A random selection of 250 physicians from each of six specialties (general practice, geriatrics, internal medicine, oncology, surgery and psychiatry) and all 127 palliative care physicians in Sweden were invited to participate in this study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
23
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 14 publications
5
23
1
1
Order By: Relevance
“…Geriatricians were less paternalistic in the 2007 study than the 2020 study; in contrast, psychiatrists and the group of youngest physicians were more paternalistic in 2007 than 2020. The main results of the 2020 study showed that most specialties, with the exception of geriatricians, were more pro-PAS in 2020 than they were in 2007 (9). (In the 2020 study, a majority of palliativists were against PAS, but no comparison to 2007 is possible.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Geriatricians were less paternalistic in the 2007 study than the 2020 study; in contrast, psychiatrists and the group of youngest physicians were more paternalistic in 2007 than 2020. The main results of the 2020 study showed that most specialties, with the exception of geriatricians, were more pro-PAS in 2020 than they were in 2007 (9). (In the 2020 study, a majority of palliativists were against PAS, but no comparison to 2007 is possible.…”
Section: Discussionmentioning
confidence: 95%
“…Although there were more arguments for physicians to prioritize in the 2007 study, we have re-calculated this prioritization so that those answers are comparable with the 2020 study. In the 2007 study, 339 (out of 614) physicians had prioritized one of the same four arguments (8) that also were part of the 2020 study and the corresponding number from the 2020 study was 617 physicians (out of 819) (9). In the 2007 study the remaining 275 physicians prioritized other arguments (8).…”
Section: Methodsmentioning
confidence: 99%
“…However, personal opinions may change with time and a study of medical students in Austria over 9 years showed that acceptance of active euthanasia increased from 16.3 in 2001 to 49.5% in 2009 [ 17 ]. Similarly, a study among physicians in Sweden in 2007 [ 18 ] showed that only 35% of respondents supported PAS (vs. 73% of public supporting the same at that time) [ 19 ], but this frequency increased to 47% when a follow-up survey was done among physicians in 2020 [ 20 ]. Interestingly in our study when ATE scores were grouped according to the scenario they represent, scores towards PAS were significantly more favourable than those for euthanasia while WLST was in between.…”
Section: Discussionmentioning
confidence: 99%
“…Both the 2007 study and the 2020 study were performed as cross-sectional surveys and were conducted as postal questionnaires with a similar structure [ 12 , 14 ]. In the 2007 study the main question was the participants’ attitude towards PAS, whereas in the 2020 study we included two additional questions regarding whether or not the participant would like to be offered PAS themselves and whether or not they were prepared to actually prescribe the needed drugs [ 14 ]. Moreover, in the 2007 survey the participants were presented with 10 fixed response arguments [ 12 ] that were either in favour of PAS or against PAS—see Box 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Two of these arguments favoured PAS—(a) based on the autonomy principle by itself and b) based on the reasoning that the autonomy principle should overrule the non-maleficence principle—and two arguments against PAS—(a) the patients do not know their own best interests and b) that the non-maleficence principle should overrule the autonomy principle. As can be seen, one of the arguments was openly paternalistic (the patients do not know their own best interests) and one argument was supposed to represent disguised paternalism (the non-maleficence principle should overrule the autonomy principle), while the remaining two arguments supported the autonomy principle [ 12 , 14 ]. The arguments that were included in the 2007 study and excluded in the 2020 study were, for example, ‘Palliative care is lacking in your region’ as a pro PAS argument and ‘Palliative care in your region is well established’ as an argument against PAS [ 12 ].…”
Section: Methodsmentioning
confidence: 99%